2021
DOI: 10.3390/ijerph18189760
|View full text |Cite
|
Sign up to set email alerts
|

Father-Teen Talks about Sex and Teens’ Sexual Health: The Role of Direct and Indirect Communication

Abstract: Family talks about sex can protect against teens’ risky sexual behavior, but most research has focused on the role of mothers. The current study included cross-sectional survey data from 728 adolescents in the 11th and 12th grades (Mage = 17.00, SD = 0.90) in the United States. Structural equation modeling (SEM) was used to assess associations between teens’ direct and indirect talk, defined as less straightforward ways to communicate one’s sexual values, with fathers about sex, and teens’ sexual behaviors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
7
1
1
Order By: Relevance
“…Direct talk, the most commonly described type of communication in this study, fits with prior findings on how parents (largely mothers) tend to communicate with teens about sex [ 49 ], and on how communication about sex is typically measured [ 5 ]. The percentage of fathers in this study who describe direct talk is higher than prior research [ 4 , 15 , 30 ], which likely reflects disproportionately high engagement in family communication among fathers who volunteered for this study. Fathers’ descriptions of indirect talk and role modeling as ways to communicate with teens suggest that some fathers may engage differently with teens than mothers around sexual issues.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Direct talk, the most commonly described type of communication in this study, fits with prior findings on how parents (largely mothers) tend to communicate with teens about sex [ 49 ], and on how communication about sex is typically measured [ 5 ]. The percentage of fathers in this study who describe direct talk is higher than prior research [ 4 , 15 , 30 ], which likely reflects disproportionately high engagement in family communication among fathers who volunteered for this study. Fathers’ descriptions of indirect talk and role modeling as ways to communicate with teens suggest that some fathers may engage differently with teens than mothers around sexual issues.…”
Section: Discussioncontrasting
confidence: 64%
“…Fathers’ descriptions of indirect talk and role modeling as ways to communicate with teens suggest that some fathers may engage differently with teens than mothers around sexual issues. A quantitative study found that more than half of teens reported indirect talk with their fathers about sex [ 30 ], an approach which may provide a way to manage discomfort in talking about sexual issues [ 50 ]. Interventions geared toward fathers may benefit from addressing multiple ways that fathers approach communication with their teens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dados do Pré-Teste (2022). As consequências da ausência de comunicação sobre sexualidade em casa são os comportamentos sexuais de risco assumidos pelos adolescentes, como início precoce da atividade sexual e relações desprotegidas, predispondo-os a contraírem IST's e/ou uma gravidez indesejada (GROSSMAN et al, 2021). Outro desdobramento é a busca de informações por parte dos adolescentes, por conta própria, que geralmente é feita em fontes inapropriadas, contribuindo para que muitas irrealidades sejam tomadas como verdades, o que impossibilita a prática segura da sexualidade.…”
Section: Fontes De Informação E Orientação Em Educação Sexualunclassified